Effects of COVID-19 lockdown on metabolic control in patients with type 2 diabetes in Sri Lanka - C. N. Antonypillai; S. C. Gunatilake; P. A. D. M. Kumarathunga; A. Zameek; G. T. Anuththra; T. I. Kodikara Arachchi; S. Tennakoon; N. S. Kalupahana (Sri Lanka Journal of Medicine, 2023)
Introduction: The COVID-19 pandemic has led to an island-wide lockdown in Sri Lanka, leading to restrictions in daily routines. The ensuing lifestyle changes have drastically influenced the prevalence and worsening of chronic diseases like diabetes with poor metabolic control of the disease. Objectives: To evaluate the immediate impact of the lockdown on the metabolic parameters associated with diabetes control in individuals with type-2 diabetes mellitus (T2DM). Methodology: A single center cross-sectional descriptive study was conducted on 157 T2DM patients attending a diabetes clinic in the private sector. Pre- and post-lockdown data on metabolic control of the study population was collected from patient records. Patients’ perceptions of diet/exercise and access to medication/medical care during the lockdown were collected through a telephone interview. Results: Pre- and post-lockdown data of 157 male (Females 88; mean age-58.68±SD 13.44 years) patients belonging to the age group 48-72 were evaluated. Of the patients who had a HbA1c of ≤ 7% pre-lockdown, 80% had shown to maintain their HbA1c. Of the patients with HbA1c > 7% pre-lockdown, 27.9% showed a reduction of their HbA1c below 7%. The majority of the responders had no difference in their diet (69.2%) and exercise (65.4%) during the lockdown. Among those with improved HbA1c (n=101;63% of cohort), 16.9% and 13% had better diet and exercise respectively while none in worsened HbA1c group had improved diet or exercise. Conclusions: Lockdown in Sri Lanka has not been associated with worsening of glycaemic control in the studied cohort of patients with type 2 diabetes. Adherence to the recommended diet and exercise regime during lockdown is associated with better glycaemic control in patients with type 2 diabetes.